Performance analysis of optimized plasmonic half-adder circuit using Mach-Zehnder interferometer for high-speed switching applications. (May 2021) - Swarnakar, Sandip; Guddati, Amrutha; Reddy, Siva Koti; Harijan, Ramanand; Kumar, Santosh
Abstract: Metal-insulator-metal (MIM, Plasmonic) waveguide has an exceptional quality of propagating the surface plasmon beyond the diffraction of light into a deep sub-wavelength scale. In this paper, the basic structure for a half-adder circuit is proposed by inducing nonlinear Kerr-material to the Mach-Zehnder interferometers (MZIs). The half-adder circuit design is optimized by using MIM plasmonic waveguide-based MZIs in the footprint of 85 μm ​× ​10 μm . Some parameters like extinction ratio, transmission efficiency, and insertion loss are calculated and found as 16.53 ​dB, 74% and 0.338 ​dB, respectively. The proposed device is concentrated in optical communication with transverse electric (TE) polarization at an operating wavelength of 1550 ​nm. This design is simulated by using the finite-difference time-domain (FDTD) technique and verified by using MATLAB simulation.